Organization Culture and Happy Workplace of Teachers in School under the Secondary Educational Service Area Office 9 - Butket, Wanlop; Onsamphan, Samroeng (Arts of Management Journal, 2020)
The research purposes were to determine 1) the organizational culture of school under the Secondary Educational Service Area Office 9 2) The happy workplace of the teacher in school under the Secondary Educational Service Area Office 3) the relationship between the organizational culture and the happy workplace of teacher’s in school under the Secondary Educational Service Area Office 9. The samples were 52 schools under the secondary educational service area office 9. The respondents in each school were a director, a deputy director or assistant director, and teachers with a total of 312. The research instrument was a questionnaire concerning the organizational culture and the happy workplace of teachers. The statistics were used to analyze data included frequency, percentage, arithmetic mean, standard deviation and Pearson’s product-moment correlation coefficient. The results of this research were as follows: The organizational culture of school under the Secondary Educational Service Area Office 9, in overall and individual, were found at a high level; ranking from descending order: Acceptance, Generosity, Honesty, Workforce Diversity, Organization Goals, Devolution, Organization Unity, Trust, Quality, and Decision making. 2.The happy workplace of teacher in school under the Secondary Educational Service Area Office collectively and individually, was found at a high level; ranking from the highest mean to the lowest mean : Happy soul , Happy Family, Happy brain , Happy heart , Happy money , Happy society, Happy body , and Happy relax . The relationship between organizational culture and the happy workplace of teacher in school under the Secondary Educational Service Area Office 9 was found at .01 level of a statistical significance.